Calling Iranian learners of L2 English: effect of gloss type on lexical retention and reading performance under different learning conditions. (5th October 2016) - Sadeghi, Karim; Khezrlou, Sima; Modirkhameneh, Sima
Abstract : This study sought to compare how three different gloss types (text–picture, text–audio and text–picture–audio) affected English as a foreign language (EFL) learners' reading comprehension and vocabulary acquisition. The study also compared how results on comprehension and vocabulary acquisition differed across three learning conditions (i.e., incidental, intentional and explicit instruction). A between‐groups design was employed with four groups ( N  = 135) of Iranian university learners of L2 English. The participants (with upper‐intermediate proficiency level) read English texts. Written recall and multiple‐choice questions were used to measure reading comprehension; vocabulary knowledge scale (VKS) and contextualized vocabulary knowledge test (CVKT) were used to assess vocabulary acquisition. Results of statistical analyses revealed that while the text–picture–audio gloss type consistently resulted in better vocabulary learning and reading comprehension, the learning conditions varied in terms of their immediate and delayed effect on vocabulary and reading scores. This study suggests that learner performances across gloss types are condition specific and provides both pedagogical and theoretical implications. What is already known about this topic Electronic glosses foster reading comprehension and vocabulary acquisition. There are different positions about the effectiveness of form focused instruction in grammar, with the focus on forms approach having a higher acceptable rate in SLA. But, this issue has been rarely researched in vocabulary acquisition. What this paper adds This study supports the complementary nature of dual annotations in vocabulary learning and reading comprehension. This study extends the issue of form focused instruction to vocabulary learning by comparing the incidental, intentional and incidental–intentional learning orientations. This study evaluates the interaction between the multiple gloss types and the learning orientations. Implications for theory, policy or practice This study provides both pedagogical and theoretical implications.